Study of Optimization of Economic Law on the Market Structure of New Energy Under the Background of Sustainable/Green Finance - Liu, Fengyun; Zhang, Zhengzhang; Song, Menglan; Chen, Jinguang (Distributed Generation & Alternative Energy Journal, 2025)
The integration of sustainable/ green finance within economic frameworks has become increasingly pivotal in driving environmentally conscious practices across enterprises, particularly within new energy markets. This study explores the optimization of economic law on the market structure of new energy within the context of sustainable finance. With the imperative to transition towards sustainable energy sources becoming increasingly urgent, understanding the interplay between economic regulations, financial mechanisms, and market dynamics is crucial. Employing multilinear regression analysis, we investigate the impact of economic law variables and sustainable finance metrics on the market structure of new energy. Through the construction of a Sobels model test, this paper seeks to comprehensively analyze the influence paths of green finance on the optimization of the market structure for new energy through the mediating effect of economic regulation. The empirical consequences of this study show that the complementary role of economic regulation impacts the potential of green finance to drive market structural improvements in the new energy sector. Also, this study employs proposed multiple linear regression analysis to explore the drivers of market dynamics in the new energy sector, with a focus on optimizing economic laws to support sustainability objectives. By broadening the scope of inquiry into the transformation of new energy enterprises, these findings offer both theoretical insights and practical guidance. The research underscores the significance of aligning financial mechanisms, regulatory frameworks, and green energy consumption to facilitate the transition towards a more sustainable and resilient market structure for new energy enterprises in China.